Lysozyme immobilization on the calcium alginate film under sonication: Development of an antimicrobial film. (October 2018) - Wang, Danli; Lv, Ruiling; Ma, Xiaobin; Zou, Mingming; Wang, Wenjun; Yan, Lufeng; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: Antimicrobial films are widely used in food and other fields. The present work established a method of preparing antimicrobial films made of calcium alginate and lysozyme. For the sake of the optimization of antimicrobial effect, sonication was applied to increase the immobilization efficiency. Different ultrasonic power and treatment duration were studied. With the assistant of sonication, lysozyme immobilization rate was speeded up and the amount of lysozyme immobilized on the supporters was increased. The catalytic activity of the antimicrobial film was measured using the turbidimetric assay and reached the maximum at 147.8 W. The antimicrobial activity determined by the inhibition zone test was also promoted by sonication. To explore the mechanism of the ultrasonic effect on the lysozyme immobilization, lysozyme structures alteration before and after ultrasonic treatment was considered. The circular dichroism and fluorescence spectra illustrated that sonication affected the secondary and tertiary structures of lysozyme. The changes in the enzyme structures may lead to the improvement of the enzymatic activity. The impact of sonication on the microstructure of the films was investigated by the scanning electron microscope. The film surface showed some cracks after sonication that increased the superficial area accordingly. Graphical abstract: Image 1 Highlights: Sonication promotes lysozyme immobilization onto the Ca-alginate film. Antimicrobial films prepared by sonication shows better bacteriostatic effect. Sonication impacts on both lysozyme and Ca-alginate structures.